Mathematical modeling and computer simulation - Maki, Daniel (Brooks/Cole / Thomson, 2006)
Two professors at Indiana University walk through the process of constructing mathematical models, and illustrate the use of stochastic processes to model several situations arising in biology, ecology, finance, political science, and psychology. The second half of the textbook explores in more detail the computer implementation of models used to study activities by simulating their actual behavior, and describes the characteristics of linear programming models for addressing business and decision making problems.